The Global Classroom: Utilizing Collaborative Platforms for Cross-Border Project-Based Learning - Iwan Adhicandra; Sibusiso Ndlovu; Jabulani Dlamini (Journal Emerging Technologies in Education, 2026)
Background. Globalization and rapid advancements in digital technologies have significantly transformed the landscape of higher education, encouraging institutions to adopt innovative learning models that transcend geographical boundaries. Collaborative digital platforms have emerged as important tools for facilitating international learning experiences, enabling students from different countries to participate in shared academic projects. Cross-border project-based learning supported by digital collaboration tools offers opportunities to enhance intercultural communication, collaborative problem-solving, and global competence among students. Despite the increasing adoption of such platforms, empirical evidence regarding their effectiveness in supporting structured global classroom environments remains limited. Purpose. This study aims to examine how collaborative digital platforms can facilitate cross-border project-based learning and to evaluate their influence on student engagement, intercultural interaction, and collaborative knowledge construction within the global classroom framework. Method. A mixed-methods research design was employed involving 120 undergraduate students from four universities participating in multinational project teams. Data were collected through questionnaires, platform interaction logs, reflective journals, and semi-structured interviews. Quantitative data were analyzed using descriptive and inferential statistics, while qualitative data were examined through thematic analysis. Results. Results indicate that collaborative digital platforms significantly enhance student engagement, intercultural communication, and collaborative problem-solving abilities. High levels of digital interaction were positively associated with improved teamwork quality and global competence development. Conclusion. The study concludes that integrated collaborative platforms provide effective infrastructures for supporting sustainable global classroom environments in higher education.